Barriers and facilitators to the implementation of prehabilitation for elderly frail patients prior to elective surgery: a qualitative study with healthcare professionals - Tamina Isabel Fuchs; Carina Pfab; Jörn Kiselev; Stefan J Schaller; Claudia Spies; Tanja Rombey (BMC, 2024)
Abstract Background Prehabilitation aims to enhance functional capacity before surgery, minimise complications and achieve a better postoperative outcome. This can be particularly useful for older, frail patients to better tolerate surgery. The aim of this study was to identify what barriers and facilitators healthcare professionals in Germany experienced in the implementation and delivery of the multimodal prehabilitation programme "PRAEP-GO" for (pre-)frail adults aged 70 years and older to inform the implementation of prehabilitation into standard care. Methods A nested descriptive qualitative study was conducted using semi-structured face-to-face interviews with healthcare professionals involved in the PRAEP-GO trial from the Berlin and Brandenburg region in Germany. Transcripts were analysed using Kuckartz' qualitative content analysis. Results were interpreted and synthesised using the Consolidated Framework for Implementation Research, a theoretical framework to allow their application to a more general context. Results A total of 14 interviews were conducted. Seven therapists (physio-, ergo-, sports therapy), five physicians and two employees from other professions with mainly administrative and organisational tasks in the project. All identified barriers and facilitating factors could be assigned to the themes of organisation, prehabilitation, cooperation and communication between healthcare professionals and with patients. Much optimisation potential was found regarding organisational aspects, e.g. addressing perceived staff shortages and optimising the patient pathway. Furthermore, it became apparent that communication and cooperation between professionals but also with patients need to be improved. More evidence regarding prehabilitation should be provided to convince professionals more. Prehabilitation should be multimodal and individualised, including the programme duration. Officially introducing prehabilitation into standard care would facilitate its delivery. Discussion These findings underscore the fact that successful implementation of prehabilitation programmes, such as PRAEP-GO, requires sufficient organisational infrastructure, human resources, access to knowledge, an adaptable and individualised programme design as well as good communication among professionals and with patients. The transferability of the findings is limited by the absence of nutritionists and resulting overrepresentation of other therapists in the sample. To further convince professionals and patients of the concept of prehabilitation, more research is needed to build a solid evidence base that will ensure greater awareness and, thus, more motivation and cooperation among professionals and patients. Trial registration Open Science Framework (osf.io/ksfgj).